Complications After Arthroscopic Knee Surgery. (February 2014) - Salzler, Matthew J.; Lin, Albert; Miller, Chealon D.; Herold, Sarah; Irrgang, James J.; Harner, Christopher D.
Background: Knee arthroscopies are among the most common procedures performed by orthopaedic surgeons, yet little is known about the associated complications and complication rates. Purpose: To examine the nature and frequency of complications after the most common arthroscopic knee procedures, with particular attention to fellowship training, geographic location of practice, and age and sex of the patient. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Data were obtained from the American Board of Orthopaedic Surgery database for orthopaedic surgeons who sat for the part II examination from 2003 to 2009. The database was queried to determine the type and frequency of complications for patients who underwent knee arthroscopy and for those who underwent sports medicine knee arthroscopy, including arthroscopic partial meniscectomy, meniscal repair, chondroplasty, microfracture, anterior cruciate ligament reconstruction, or posterior cruciate ligament reconstruction. Factors affecting complication rates that were investigated included type of procedure, fellowship training status, geographic location of practice, and age and sex of the patient. Results: There were 4305 complications out of 92, 565 knee arthroscopic procedures obtained from the American Board of Orthopaedic Surgery database for an overall candidate-reported complication rate of 4.7%. The complication rates were highest for posterior cruciate ligament reconstruction (20.1%) and anterior cruciate ligament reconstruction (9.0%); complication rates for meniscectomy, meniscal repair, and chondroplasty were 2.8%, 7.6%, and 3.6%, respectively. The complication rate for sports fellowship–trained candidates was higher than for non–sports trained candidates (5.1% sports, 4.1% no sports; P < .0001) and for male patients (4.9% male vs 4.3% female; P < .0001). Younger patients (<40 years; 6.2%) had a higher complication rate than older patients (≥40 years; 3.58%) ( P < .0001). Procedure complexity is a likely confounding factor affecting sports-trained candidates and younger patients. There were no geographic differences ( P = .125). The overall rate of pulmonary embolus was 0.11%. Surgical complications (3.68%) were more common than medical (0.77%) or anesthetic complications (0.22%), and infection was the most common complication overall (0.84%). Conclusion: The overall self-reported complication rate for arthroscopic knee procedures was 4.7%. Knee arthroscopy is not a benign procedure, and patients should be aware of the risk of complications.